The effect of the competitive season in professional basketball on inflammation and iron metabolism - A Dzedzej; W Ignatiuk; J Jaworska; T Grzywacz; P Lipińska; J Antosiewicz; A Korek; E Ziemann (Termedia Publishing House, 2016)
Following acute physical activity, blood hepcidin concentration appears to increase in response to exercise-induced inflammation, but the long-term impact of exercise on hepcidin remains unclear. Here we investigated changes in hepcidin and the inflammation marker interleukin-6 to evaluate professional basketball players' response to a season of training and games. The analysis also included vitamin D (25(OH)D3) assessment, owing to its anti-inflammatory effects. Blood samples were collected for 14 players and 10 control non-athletes prior to and after the 8-month competitive season. Athletes' performance was assessed with the NBA efficiency score. At the baseline hepcidin correlated with blood ferritin (r=0.61; 90% CL ±0.31), but at the end of the season this correlation was absent. Compared with the control subjects, athletes experienced clear large increases in hepcidin (50%; 90% CI 15-96%) and interleukin-6 (77%; 90% CI 35-131%) and a clear small decrease in vitamin D (-12%; 90% CI -20 to -3%) at the season completion. Correlations between change scores of these variables were unclear (r = -0.21 to 0.24, 90% CL ±0.5), but their uncertainty generally excluded strong relationships. Athletes were hence concluded to have experienced acute inflammation at the beginning but chronic inflammation at the end of the competitive season. At the same time, the moderate correlation between changes in vitamin D and players' performance (r=0.43) was suggestive of its beneficial influence. Maintaining the appropriative concentration of vitamin D is thus necessary for basketball players' performance and efficiency. The assessment of hepcidin has proven to be useful in diagnosing inflammation in response to chronic exercise.